2011
DOI: 10.5539/elt.v4n4p10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computer-Assisted Whole Language Instruction on Taiwanese University Students’ English Learning

Abstract: The purposes of this study are: (1) to investigate students' perceptions of computer-assisted whole language instruction; (2) to examine the effectiveness of whole language instruction on students' reading improvement; and (3) to determine the difference between basic-level and advanced-level students' improvement in reading skills. A total of 212 freshmen (98 low level and 114 high level students) were quasi-randomly selected as the participants of the survey study. Instruments included a questionnaire and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Their fantasy cannot be stimulated by a fairytale/story. The fantasy of children with intellectual disability attached to concrete circumstances and fixed complexes [20]. Reading for them will consist of words in motions and lips pattern as a substitute for the sounds of vowel, consonant, and intonation [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their fantasy cannot be stimulated by a fairytale/story. The fantasy of children with intellectual disability attached to concrete circumstances and fixed complexes [20]. Reading for them will consist of words in motions and lips pattern as a substitute for the sounds of vowel, consonant, and intonation [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature further recognizes a growing body of research findings which claim the influence of theories that relate language learning and literacy to the integrated approach in classroom contexts. These include the socio-psycholinguistic theory which bridges the cognitive and linguistic activities in a social context (Bridge 2011), the socio-cognitive theory of learning which recognizes the holistic model of learning where learners use their social conceptual experiences and language knowledge to engage in mental dialogue (Wang 2011), and humanistic and constructivist theories of learning which recognize the integrated approach as authentic, personalized, self-directed and collaborative (Richards & Rogers 2001;Illeris 2009;Çekiç 2010). These theoretical foundations, however, collectively claim the centrality of learners' experiences and activities relevant to their lives and needs, as well as authentic materials that can be used to enhance language practices.…”
Section: Integrated Approach To Language Learning and Teachingmentioning
confidence: 99%
“…It has been observed by the TESOL Professor, Writer and Consultant, Ken Beatty (2013), author/co-author of more than 130 ESL textbooks used worldwide from the primary to tertiary levels, that computers increasingly play an important role in education particularly language learning. Furthermore, Wang (2011) has conducted various studies on the competence and efficacy of computer technology and the software programs on teaching of writing. He has found that about 80% of language learners agreed that the incorporation of CALL into language learning has encouraged them and boosted their interest in learning English writing.…”
Section: Introductionmentioning
confidence: 99%